Pengaruh Independensi dan Keahlian Komite Audit Terhadap Manajemen Laba Riil dengan Kualitas Audit Sebagai Variabel Moderasi - Ditta Dwi Astuti; Lidya Primta Surbakti; Aniek Wijayanti (Penerbit Goodwood, 2021)
Purpose: This study aimed to analyze the influence of the audit committee's independence and expertise on real earnings management by using audit quality as the moderating variable and firm size, leverage, and profitability as control variables. Research Methodology: Real earnings management was processed by Roychowdhury’s model and it used the abnormal value of operating cash flow, discretionary expenses, and production costs. This study used secondary data from annual reports of non-financial companies listed on the Indonesia Stock Exchange for the period 2017-2019 and the total was 516 companies. This study used panel data regression and was processed by Stata. Results: This study proves that audit committee independence and leverage have a significant negative effect on real earnings management through discretionary expenses and audit quality cannot moderate the relationship between audit committee independence and audit committee expertise on real earnings management. Limitation: The study used audit quality as moderating variable. However, the results cannot prove that audit quality is able to affect real earnings management. Contribution: The results obtained can be used for investors' and creditors' consideration when making investment or loans decisions and can be references for further research.